Near-Infrared Aggregation-Induced Emission-Active Probe Enables in situ and Long-Term Tracking of Endogenous β-Galactosidase Activity - Fu, Wei; Yan, Chenxu; Zhang, Yutao; Ma, Yiyu; Guo, Zhiqian; Zhu, Wei-Hong (Frontiers in Chemistry, 2019)
High-fidelity tracking specific enzyme activities is critical for the early diagnosis of diseases such as cancers. However, most of available fluorescent probes are difficult to obtain in situ information because of tending to facilely diffusion or inevitably suffering from the aggregation-caused quenching (ACQ) effect. In this work, we developed an elaborated near-infrared (NIR) aggregation-induced emission (AIE)-active fluorescent probe, which is composed of a hydrophobic 2-(2-hydroxyphenyl) benzothiazole (HBT) moiety for extending into NIR wavelength, and a hydrophilic β-galactosidase (β-gal) triggered unit for improving miscibility and guaranteeing its non-emissive in aqueous media. This probe is virtually activated by β-gal, and then specific enzymatic turnover would liberate hydrophobic AIE luminogen (AIEgen) QM-HBT-OH. Simultaneously, brightness NIR fluorescent nanoaggregates are in situ generated as a result of AIE-active process, making on-site the detection of endogenous β-gal activity in living cells. By virtue of NIR AIE-active performance of enzyme-catalyzed nanoaggregates, QM-HBT-βgal is capable of affording a localizable fluorescence signal and long-term tracking of endogenous β-gal activity. All results demonstrate that the probe QM-HBT-βgal is a powerful molecular tool to better understand the biological roles of β-gal activity, attaining high-fidelity information in preclinical applications.